1994
DOI: 10.1055/s-2007-1016489
|View full text |Cite
|
Sign up to set email alerts
|

Aorto-Caval Fistula - an Uncommon Complication of Infrarenal Aortic Aneurysms

Abstract: Aorto-caval fistulas are an uncommon complication of infrarenal aortic aneurysms, being found in 0.22% to 6.04% of all cases. Operating on 1231 patients with abdominal aortic aneurysm in the last 30 years we saw 17 patients with an aortocaval fistula. While 5 patients showed an isolated fistula, 12 had an additional rupture of the aneurysm into the retroperitoneal space or the abdominal cavity. Only in four patients was the aorto-caval fistula diagnosed preoperatively. In 16 patients the fistula was closed fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
68
0
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(70 citation statements)
references
References 5 publications
1
68
0
1
Order By: Relevance
“…2 Besides atherosclerotic aneurysms, which represent the majority, other causes are syphilitic, mycotic aneurysms secondary to Marfan's syndrome, Ehlers-Danlos syndrome, Takayasu arteritis, 4-7 after surgery for herniated lumbar disc 8 and secondary to abdominal penetrating or, more rarely, blunt traumas. 9,10 Many series including a small number of cases report diagnostic difficulty.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Besides atherosclerotic aneurysms, which represent the majority, other causes are syphilitic, mycotic aneurysms secondary to Marfan's syndrome, Ehlers-Danlos syndrome, Takayasu arteritis, 4-7 after surgery for herniated lumbar disc 8 and secondary to abdominal penetrating or, more rarely, blunt traumas. 9,10 Many series including a small number of cases report diagnostic difficulty.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 We report a case of of common iliac and right internal artery aneurysm with fistula into the common iliac vein, whose initial presentation was right lower limb (RLL) edema and dyspnea, causing diagnostic confusion with deep venous thrombosis and pulmonary embolism.…”
Section: Introductionmentioning
confidence: 99%
“…Aorto-caval fistula (ACF) is a rare entity, complicating about 0.2-6.04% of all abdominal aortic aneurysms (1,2).…”
Section: Introductionmentioning
confidence: 99%
“…Before wide implementation of spiral and multislice computed tomography (CT), some studies reported about 75% of preoperatively undiagnosed cases of ACF (1). Specific signs of ACF on CT enable the prompt and accurate diagnosis (2)(3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%
“…Aortocaval fistula is a rare entity, complicating about 0.2-0.04 % of all abdominal aortic aneurysms [1,2]. Rare causes include mycotic aneurysm, lues, and disorders of connective tissue, such as the Ehlers-Danlos and Marfan syndromes [3].…”
mentioning
confidence: 99%